Implication of Transitive Verbs among the Meaning of Intransitive Verbs in Qur’an as Example - เจะมะ อานีซะห์ (Al-HIKMAH Journal, 2021)
This study aims to find out the phenomenon of implication in Arabic syntax, Emphasizing on the implication of transitive verbs among the meaning of intransitive verbs. The study has followed implication places in verses of Qur’an, in the purpose of extracting meanings related to the transitive verbs when they implicate the meanings of intransitive verbs, as well as presented the using of those verbs in their original feature, via some of evidence form hadith. The researchers relied on this study on descriptive and Analytical methods. As result, the researchers found that the implication of a verb is that the verb guarantees the meaning of another verb and works with the meaning of implication, it is commonly used in Qur’an until it becomes like an original.